Sex-mismatching in isolated heart transplantation confers no postoperative risk - Reid Dale, PhD; Matt Leipzig, BSc; Nataliya Bahatyrevich, MD; Katharine Pines, MPH; Qiudong Chen, MD; Jeffrey Teuteberg, MD; Y. Joseph Woo, MD; Maria Currie, MD, PhD (JHLT Open, 2024)
Background: For heart transplantation, optimal donor-recipient matching is an important factor in the ongoing development of the United Network for Organ Sharing (UNOS) continuous distribution framework. Donor-recipient sex-mismatch has decreased since the 1990s, but this may be related to the risk posed by size mismatching, particularly when donor hearts are undersized. Thus, the impact of sex-mismatching, controlling for other factors including size mismatch, is uncertain. Methods: Adult first-time, isolated heart transplant patients from the UNOS database between October 1, 1987 and December 31, 2022 were analyzed. Cohorts were separated into male and female recipients. Propensity score matching on known preoperative risk factors was performed. Equivalence testing via Two One-Sided Testing (TOST) was performed to assess between-arm equivalence in postoperative outcomes. Survival differences were measured by the between-arm ratio of restricted mean survival time and binary outcome differences by the odds ratio. Results: In the propensity-matched cohort, we found significant equivalence between arms in both male (TOST p < 0.001) and female (TOST p < 0.001) recipients for overall survival at all temporal end-points, postoperative treatment for rejection within 1 year, and predischarge dialysis. Conclusions: Sex-mismatch in isolated heart transplantation confers no additional risk to postoperative outcomes when controlling for other factors, including size mismatch. Consequently, sex-mismatch should not factor into individual assessments of organ acceptance or be incorporated into any national organ allocation policy. Increasing the acceptance of sex-mismatched donors has the potential to expand the donor pool and increase female donor utilization.